Szkice i obrazy Kartezjusza - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2026)
Today, Descartes’ writings are widely available in academic circles and beyond. However, they had to fight hard to gain this right of presence. There was a time when it was easier for them to find their way onto the Church’s Index of Prohibited Books than to cross the gates of universities or even reach people interested in philosophical novelties. In these reflections, I attempt to answer the question: what was the “stumbling block” for the Church censors? Not only for them, but also for those theologians and philosophers who had greater faith in God’s powers than in their own reason. It seems indisputable that Descartes relied on reason. What is debatable, however, is whether he anticipated such a negative reaction from those around him, and whether he did enough to convince readers of his works who were open to serious discussion to accept his vision of man, the world and God.